Dose-Dependent Cognitive Decline, Anxiety, and Locomotor Impairments Induced by Doxorubicin: Evidence from an Animal Model - Ângela Amaro-Leal; Ana I. Afonso; Filipa Machado; Liana Shvachiy; Isabel Rocha; Tiago F. Outeiro; Vera Geraldes (Biology)
Cognitive impairment and anxiety are common side effects of chemotherapy, particularly with the use of doxorubicin (DOX), known as “chemobrain”. This study aimed to examine the dose-dependent effects of DOX on cognitive decline, anxiety, and locomotor activity in healthy female Wistar rats. The rats were divided into groups receiving low (2 mg/kg), intermediate (4 mg/kg), and high (5 mg/kg) doses of DOX for four weeks, alongside a control group. Behavioral tests, including open field, elevated plus maze, and Y-maze tests, assessed anxiety, locomotion, and cognitive performance, while brain tissue analysis evaluated neuroinflammation using markers such as GFAP and Iba-1. The results showed that all doses of DOX induced anxiety-like behavior, reduced locomotion, and caused neuroinflammation in the hippocampus, with more severe effects at higher doses. Notably, high-dose DOX also caused short-term memory deficits. These findings highlight the dose-dependent nature of DOX’s impact on behavior and cognition, suggesting that DOX plays a key role in the development of cognitive symptoms during chemotherapy. Further research is needed to understand the mechanisms behind these effects and to explore potential interventions.